Breaking Lockdown during Lockdown: A Neutralization Theory Evaluation of Misbehavior during the Covid 19 Pandemic. Issue 7 (3rd July 2022) - Harris, Lloyd C.
ABSTRACT: The Covid-19 pandemic constitutes a global crisis that has necessitated many nations to adopt and enforce various strategies to reduce the spread of the virus, protect citizens, and alleviate pressures on healthcare systems. Central to such reactions are 'lockdown' regulations that limit travel, require restricted movement by citizens, and enforce stay-at-home rules. However, while evidence suggests general (but not unanimous) support for the principles of such lockdowns, reports also indicate that individuals are far from universally compliant. In this regard, lockdown rule breaking may be viewed as a form of misbehavior. The aim of this study is to explore and explicate if, and if so, how and why citizens deviate from espoused lockdown rules and neutralize or justify their guilt. In order to do so, we utilize the theory of neutralization as our conceptual lens of analysis. Using in-depth interviews of individuals experiencing lockdown conditions, we analyze neutralization techniques to lockdown infringements. Our analysis suggests that the guilt of rule transgressions is neutralized in two main ways; via the denial of deviance and the negation of the espouse lockdown norm. Insights are generated in specific forms of neutralization and wider implications discussed.